Consumption by healthy adults of pasteurized milk with a high concentration of Bacillus cereus: a double-blind study - Langeveld, L.P.M. (NIZO, Bilthoven, The Netherlands.); Spronsen, W.A. van; Beresteijn, E.C.H. van; Notermans, S.H.W (Journal of food protection, 1996)
A double-blind experiment with 34 healthy human volunteers, aged between 20 and 60 years, was conducted to obtain information about the allowable concentration of B. cereus in pasteurized milk. During a period of 3 weeks the subjects were exposed to B. cereus naturally present in pasteurized milk following storage for 3 to 14 days at 7.5 degrees C. Of 259 milk exposures, gastrointestinal complaints were observed in 18 cases. According to total numbers of B. cereus ingested per exposure the complaints per number of exposures were distributed as follows: 10(6): 5 in 132; 10(6) to 10(7): 2 in 32; 10(7) to 10(8): 2 in 26; and 10(8): 9 in 69. Symptoms, however, were not typical of those caused by B. cereus. There was a weak significance (P less than or equal to 0.1) for symptoms when 10(8) B. cereus cells were ingested. Milk with 10(6) to 10(7) B. cereus cells per ml showed a very low diarrheal enterotoxin titer. Pure cultures of B. cereus strains isolated from samples with high B. cereus concentrations also showed a low production of enterotoxin. It can be concluded that for healthy adults the probability of become diseased from cold-stored pasteurized milk is small. From the results no evidence is obtained that B. cereus concentrations less than 10(5)/ml will cause intoxication